Achieving the Food Security Strategy by Quantifying Food Loss and Waste. A Case Study of the Chinese Economy - Daniel Durán-Sandoval (MDPI AG, 2021)
Undernourished and food insecurity are recognized as two highly relevant topics. Approximately 820 million people in the world are undernourished and 2 billion people have moderate or severe food insecurity (FAO). In addition, globally roughly one-third of food is not consumed and is wasted. This article aims to provide an updated estimate of food loss and waste (FLW) in China as, in the period 2016–2018, there were still 122 million people in this country experiencing undernourishment. In this research, we use a top-down mass balance approach, discuss how it affects the achievement of SDG 2, Zero Hunger, that it is linked also to target 12.3 that “seeks to halve global food waste at retail and consumer levels, as well as to reduce food loss during production and supply” (United Nations). We point out some challenges that private and public policies still need to overcome to reduce FLW. The results of this research may contribute a more accurate baseline for the design of public policies and strategies related to FLW and the corresponding SDGs.